C-reactive protein as a screening test for gestational diabetes mellitus in first-trimester of pregnancy: a prospective cohort study - Farghaly, Tarek A.; Helmy, Neveen A.; Abbas, Ahmed M.; M. Ahmed, Abdel Ghaffar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The current study aims to determine if increased inflammation identified by increased C-reactive protein (CRP) level is associated with the subsequent development of gestational diabetes mellitus (GDM). Methods: A prospective cohort study conducted at a tertiary University Hospital included 496 booking for their antenatal care visit between 10-12 weeks of gestation. They were tested for presence of CRP in blood. All women without a history of antenatal type 1 or type 2 diabetes undergo routine GDM screening with the 50-g oral glucose-loading test (GLT) between 24 and 28 weeks 'gestation. Women whose 1-h post-loading plasma glucose level >7.8 mmol/l (>140 mg/dl) undergo a diagnostic, fasting, 100-g, 3-h oral glucose tolerance test (OGTT) within 1-2 weeks following the GLT. Results: Among these 496 women, a total of 27 women (5.4%) were diagnosed as GDM and 10 women (2.0%) were diagnosed as IGT at week 24-28. The CRP was positive and higher in the GDM diagnosed group (p=0.000) compared to those who did not develop GDM. CRP was positively correlated with diagnosis of GDM (r=0.438, p=0.012). Conclusions: There is an association between first-trimester inflammation, marked by increased CRP levels and subsequent risk of GDM.